Developing Android-based Application of Handball Match Statistics for the Coaches in East Kalimantan (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
One of the support branches of the handball sport can be developed with using easy technology which is simple and cheap. The objective of this study is to develop and analyze the product of the android-based application of handball match statistics, the acceptability and effectiveness of the android-based application of handball match statistics on the coach’s evaluation. The research procedure included several steps: identification of potential and problems; data collection; product design; expert validation; revision; small-scale trial; product revision; large-scale trial; product revision. The instruments used in this study were evaluation sheet/questionnaire, and suggestion. The validation results of materials experts I and II were obtained from the materials and content quality by the percentage of 75% in step I and 88% in step II from the materials expert I, and by percentage of 81% in the step I and 90% in the step II from the materials expert II. In a small-scale trial, the score obtained from the coach was in a very good category with the average percentage of 83%. The results of large-scale product trial obtained a score in the very good category with the average percentage of 88%. The results of product trial obtained the average percentage of 88% in the very good category. The conclusion of this study develops an android-based application product of handball match statistics. The suggestion is this application can be used by coaches during a match to evaluate the match quickly.